Household Environmental Practice for Prevent and Control Dengue Fever toward One Health Framework in an Endemic Area of Central Region, Thailand - Weerawat Ounsaneha (2022)
This research aimed to determine the household environment practice (HEP) among the community setting in the central region of Thailand for dengue prevention and control. For 422 household respondents in three villages with high dengue morbidity rates in Central Region of Thailand were systematically selected in this cross-sectional survey. The household representatives were interviewed using a structured questionnaire for measuring good HEP and household survey by entomologic indices. Univariate and Multivariate analysis were performed to investigate the predictive factors for HEPs. The results revealed that 72.7% of the respondents had a high level of knowledge. More than half (53.8%) of the participants had positive attitudes for HEP toward one health concept, respondents with a positive attitude, had good personal preventive behaviors, vector control management, social support, and good community participation were more likely to support HEPs (p-value < 0.001). The entomologic survey on House index, Container index, and Breteau index indicated that urgent prevention and control were required in three endemic areas. From the finding of this research recommend that the community at endemic areas should implement the one health training program which provides knowledge and practices on one health, encourage collaborations with all stakeholders, and promote multi-disciplinary approach.